Notational analysis of elite and sub-elite water polo matches - Lupo, C.; Tessitore, A.; Minganti, C.; Capranica, L. (The Journal of Strength and Conditioning Research, 2010)
This study aimed at comparing elite (i.e., Euro League and Italian "Serie A1") and sub-elite (Italian "Serie B") matches. A notational analysis was performed on 17 men's water polo matches during the 2005-2006 season to evaluate the following technical and tactical parameters of the offensive play: frequency of occurrence of the actions; mean clock-time duration; mean number of players involved and passes; frequency of occurrence of the turnovers; and frequency of occurrence of the number, outcome, position, and type of the shots. All the indicators were analyzed in relation to even (i.e., equal number of offensive and defensive players), counterattack (i.e., higher number of offensive players than that of the defense), and power play (i.e., a team defending for 20 seconds without a player because of an exclusion foul) situations. A multivariate approach (multivariate analysis of variance) was applied to the playing situations (even, counterattack, and power play) as dependent variables and competition levels (Final Four of Euro League Championship, Serie A1 Championship, and Serie B Championship) as between factor (p < 0.05). Significant differences among competition levels emerged in (a) the frequency of occurrence of counterattack and power play actions, (b) the duration of even situations, (c) the mean number of players directly involved during power play actions, (d) the mean number of the passes during even and power play actions, (e) the frequency of occurrence of the shots during counterattack and power play actions, (f) the frequency of occurrence of goals during even actions, (g) the frequency of occurrence of shots originating from different zones of the court, and (h) the type of shots performed. The present results showed that the competition level has a relevant impact on the occurrence of technical and tactical indicators especially in relation to even, counterattack, and power play situations. Thus, notational analysis proved to be a valuable tool for better coaching through the interpretation of technical and tactical aspects of water polo in relation to its competition level.